2021
DOI: 10.1177/1046496421997889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ICT Shared Mental Models on Team Processes and Outcomes

Abstract: Although existing studies have shown that shared mental models of information and communication technology (ICT shared mental models) are related to better computer-mediated teamwork, causal effects on team processes and outcomes remain unclear. This study analyzes the effects of ICT shared mental models on team effectiveness indicators via ICT use and team communication. Results based on 69 three-person teams show that manipulated ICT shared mental models significantly influence team performance, coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Not being aware of SMMs prevents team members from drawing upon them, and this limits their ability to predict or understand each other’s behaviour (Rentsch et al , 2009). While research on perceived SMMs is sparse, some recent studies (Marhefka et al , 2020; Müller and Antoni, 2020, 2022) have started to address the call for greater understanding of such perceptions of SMMs and how they influence team performance (Mohammed et al , 2010, 2021). For example, Marhefka et al (2020) conducted a study with virtual teams and found that perceived temporal mental model similarity positively predicts team viability but negatively predicts team performance.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Not being aware of SMMs prevents team members from drawing upon them, and this limits their ability to predict or understand each other’s behaviour (Rentsch et al , 2009). While research on perceived SMMs is sparse, some recent studies (Marhefka et al , 2020; Müller and Antoni, 2020, 2022) have started to address the call for greater understanding of such perceptions of SMMs and how they influence team performance (Mohammed et al , 2010, 2021). For example, Marhefka et al (2020) conducted a study with virtual teams and found that perceived temporal mental model similarity positively predicts team viability but negatively predicts team performance.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Importantly, without a mutual awareness that the mental model of each individual in a dyad is similar to that of the other – i.e. perceived SMM similarity – team members may not reliably act on and hence benefit therefrom (Burtscher and Oostlander, 2019; Marhefka et al , 2020; Müller and Antoni, 2020, 2022; van Rensburg et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In post-pandemic times, teaching will remain online to some extent, and digital elements and platforms will be integrated into in-person teaching. Teachers and students should ensure transparent rules so that shared mental models specifying when, why, and how to use which ICT can emerge ( Müller & Antoni, 2022 ).…”
Section: Concluding Lessons Learned Beyond Pandemic Timesmentioning
confidence: 99%
“…Information and communication technology advances have contributed to the increased popularity of the VPT [6]. When it comes to virtual teams, technology can be a valuable tool, which enables group members to communicate effectively [6,10,11]. The choice of the communication medium affects the social dynamics within virtual teams [13].…”
Section: ░ 2 Literature Reviewmentioning
confidence: 99%